Cuproptosis patterns in papillary renal cell carcinoma are characterized by distinct tumor microenvironment infiltration landscapes - Zhang, Chiyu; Huang, Ruizhen; Xi, Xiaoqing (Frontiers in Molecular Biosciences, 2022)
Cuproptosis is a novel kind of programmed cell death that has been linked to tumor development, prognosis, and responsiveness to therapy. Nevertheless, the precise function of cuproptosis-related genes (CRGs) in the tumor microenvironment (TME) remains unknown. We characterized the genetic and transcriptional changes of CRGs in papillary renal cell carcinoma (PRCC) samples and analyzed the expression patterns in two separate cohorts. We identified two unique molecular subgroups and discovered that multi-layer CRG mutations were associated with clinicopathological features, prognosis, and TME features in patients. Then, a risk score for predicting overall survival (OS) was created and validated in patients with PRCC. To make the risk score more clinically useful, we created a nomogram that was very accurate. A lower risk score, which was associated with higher mutation load, and immune activity, suggested a better prognosis for OS. Additionally, the risk score was shown to be substantially linked with the drug's susceptibility to chemotherapeutic agents. Our extensive research of CRGs in PRCC identified possible roles for them in the TME, clinicopathological features, and overall survival. These findings may help advance our knowledge of CRGs in PRCC and pave the way for improved prognosis and the creation of more effective immunotherapy therapies.